PENGENAAN PAJAK PADA PERJANJIAN PENGIKATAN JUAL BELI HAK ATAS TANAH DI DENPASAR - Sudini, Luh Putu; Hasibuan, Nella; Wiryani, Made (DiH: Jurnal Ilmu Hukum, 2020)
-Considering that tax is one of the sources of state revenue originating from public contributions to the State treasury. According to Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, Indonesia is a rule of law. Tax collection based on laws that can be forced without the services of compensation (contravention) that can be directly demonstrated and used to pay for public expenditure and the construction of public facilities. Taxes in Indonesia are currently one of the largest sources of revenue for the nation's development in order to achieve prosperity for its citizens. The act of buying and selling is an agreement between the parties about paying a certain price of an item, with the aim of transferring ownership rights to the material sold. To achieve legal certainty in the sale and purchase of land rights, the parties are bound by an agreement based on an agreement made before a Notary. Problem formulation: 1. What is the process of binding the sale and purchase of land rights related to taxation in Denpasar? And 2. What are the forms of tax imposition in to buy and sell rights to land in Denpasar? This research is empirical legal research. The binding agreement on the sale and purchase of land rights is a pre-agreement made related to the imposition of tax in the case of a transfer of rights to land that must be paid in advance in order to carry out trading transactions before the Land Deed Maker Officer. The tax imposed from the binding agreement on the sale and purchase of land rights is the income tax for the seller and the Fees for Acquiring Land and/or Building Rights (BPHTB) for the buyer.Mengingat pajak merupakan salah satu sumber penerimaan Negara yang berasal dari iuran rakyat kepada kas Negara. Menurut Pasal 1 ayat (3) Undang-Undang Dasar Negara Republik Indonesia 1945, Indonesia merupakan Negara hukum. Pemungutan pajak berdasarkan undang-undang yang dapat dipaksakan dengan tiada mendapat jasa imbalan (kontraprestasi) yang dapat langsung ditunjukkan dan digunakan untuk membayar pengeluaran umum dan pembangunan fasilitas umum. Pajak di Indonesia saat ini menjadi salah satu sumber penerimaan terbesar pembangunan bangsa dalam rangka mencapai kesejahteraan bagi warga negaranya. Tindakan jual beli merupakan suatu kesepakatan antara para pihak tentang membayar harga tertentu dari suatu barang, dengan tujuan mengalihkan hak milik atas kebendaan yang  dijual. Untuk mencapai kepastian hukum pada jual beli hak atas tanah, para pihak diikat dengan suatu perjanjian berdasarkan kesepakatan  yang di buat di hadapan Notaris. Rumusan masalah: 1. Bagaimana  proses pengikatan jual beli hak atas tanah terkait dengan pengenaan pajak di Denpasar? Dan 2. Bagaimana bentuk pengenaan pajak dalam pengikatan jual beli hak atas tanah di Denpasar? Penelitian ini merupakan penelitian hukum empiris. Perjanjian pengikatan jual beli hak atas tanah merupakan pra-perjanjian yang  dibuat terkait dengan pengenaan pajak dalam hal peralihan hak atas tanah yang harus di bayarkan terlebih dahulu agar dapat melakukan transkasi jual beli di hadapan Pejabat Pembuat Akta Tanah. Pajak yang dikenakan dari perjanjian pengikatan jual beli hak atas tanah yakni pajak penghasilan bagi pihak penjual dan Bea Perolehan Hak Atas Tanah Dan/Atau Bangunan (BPHTB) bagi pihak pembeli.